Most common causes of unfitness of blood and hemoderivative donors according to sex - Mingrone, Claudia; Guimarães, Maria Gabriela; Borges, Luiz Carlos; Penhalber, Eduarda; Basilio, Raquel; Cortez, Afonso José (Brazilian Journal of Global Health, 2022)
OBJETIVO: A doação de sangue no Brasil é marcada por um histórico turbulento de hemoterapia descentralizada, sem políticas eficientes. O Artigo 64 da Lei Federal n° 10.205/2001 exige que antes da doação, os candidatos passem por um processo sigiloso de triagem. Essa etapa é subdividida em: registro, triagem clínica e sorológica. Posteriormente, é considerado apto, com inaptidão definitiva ou temporária. Comparar as principais causas de inaptidão para doação de sangue entre homens e mulheres dos hemocentros da entre os anos de 2017 e 2020. MÉTODOS: Estudo observacional e retrospectivo, de abordagem quantitativa e qualitativa. Informações tabuladas dos anos de 2017 a 2020 foram extraídas da base de dados do hemocentro. RESULTADOS: Análise feita pela comparação entre as causas de inaptidão, no caso a somatória entre homens e mulheres entre os anos de 2017 e 2020. Dentre as 5 causas de inaptidão para homens, 4 se repetem em todos os anos, sendo elas: uso de medicamentos em todos os anos, automedicação e/ou necessidade efetiva para doenças crônicas; cirurgia recente; relação sexual de risco; Hipertensão arterial. Dentre as 5 causas de inaptidão para mulheres 4 se repete em todos os anos: uso de medicamentos, cirurgia recente, hematócrito/hemoglobina baixa; Tatto/Acupuntura/Perfuração do lóbulo da orelha. CONCLUSÃO: Ao elencar os principais fatores de exclusão para doação entre os sexos, é perceptível que as causas se mantêm constantes ao longo dos anos. DESCRITORES: Seleção do Doador, Doadores de Sangue, Distribuição por Sexo, Hemovigilância, Estudo observacional. ABSTRACT OBJECTIVE: Blood donation in Brazil is marked by a turbulent history of decentralized hemotherapy, without efficient policies. Article 64 of Federal Law No. 10,205/2001 requires that, prior to donation, candidates undergo a confidential screening process. This step is subdivided into: registration, and clinical and serological screening. Subsequently, the donor is considered fit, or as presenting permanent or temporary unfitness. Thus, the objective was to compare the main causes of unfitness to donate blood among men and women from blood centers between 2017 and 2020. METHODS: Observational and retrospective study, with a quantitative and qualitative approach. Tabulated information for the years 2017 to 2020 was extracted from the hemocenter database. RESULTS: Analysis was performed by comparing the causes of unfitness, in this case the sum between men and women, between the years 2017 and 2020. Among the 5 causes of unfitness for men, 4 are repeated every year, namely: use of medication, self-medication, and/or effective need for chronic diseases; recent surgery; risky sexual intercourse; arterial hypertension. Among the 5 causes of disability for women, 4 are repeated every year: medication use; recent surgery; low hematocrit/hemoglobin; tattoo/acupuncture/ear lobe piercing. CONCLUSION: When listing the main exclusion factors for donation between the sexes, it is noticeable that the causes remain constant over the years. DESCRIPTORS: Donor Selection, Blood Donors, Sex Distribution, Hemovigilance, Observational Study.